2010
DOI: 10.1007/s11248-010-9424-3
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Beet necrotic yellow vein virus p25 protein induces hormonal changes and a root branching phenotype in Arabidopsis thaliana

Abstract: The RNA-3-encoded p25 protein was previously characterized as one of the major symptom determinants of the Beet necrotic yellow vein virus. Previous analyses reported the influence of the p25 protein in root proliferation phenotype observed in rhizomania disease on infected sugar beets (Beta vulgaris). A transgenic approach was developed, in which the p25 protein was constitutively expressed in Arabidopsis thaliana Columbia (Col-0) ecotype in order to provide new clues as to how the p25 protein might promote a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 58 publications
0
28
0
1
Order By: Relevance
“…Such findings can lead directly to the development and testing of management practices for improved economic yields, water use efficiency and nutrient foraging. Recent work in model systems has demonstrated that virus infections can lead to alterations in lateral root development [22], [23], [24]. These findings provide evidence about the potential influence of biotic factors on root architecture development.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…Such findings can lead directly to the development and testing of management practices for improved economic yields, water use efficiency and nutrient foraging. Recent work in model systems has demonstrated that virus infections can lead to alterations in lateral root development [22], [23], [24]. These findings provide evidence about the potential influence of biotic factors on root architecture development.…”
Section: Introductionmentioning
confidence: 73%
“…In the past, information on morphological, hormonal, and molecular characterizations of virus infection on roots have been limited [34], [35], but new findings are beginning to reveal the integrative role of auxin in mediating virus effects on root architecture. For example, Arabidopsis plants that were transformed to express the Beet necrotic yellow vein virus p25 protein showed abnormal root branching, accompanied by significant changes in the levels of auxin, jasmonic acid and ethylene precursor, ACC [24]. In another study, Cucumber mosaic virus -infected Arabidopsis root growth patterns were accompanied by significant changes in indole-3-acetic acid (IAA), trans -zeatin riboside and dihydrozeatin riboside [25].…”
Section: Discussionmentioning
confidence: 99%
“…The smaller RNAs (RNA3, RNA4, and, when present, RNA5) are dispensable for infection of laboratory hosts upon mechanical inoculation but are required for the natural infection of Beta species and for transmission of the virus. RNA3 influences symptom expression in host plants through its p25 protein [10,11]. RNA3 is also essential for BNYVV long-distance movement in Beta species, but this does not require p25, as p25-deficient RNA3 still moves long distances [12].…”
Section: Introductionmentioning
confidence: 99%
“…The classic symptoms of rhizomania are expansive numbers of secondary roots that give the main taproot a bearded appearance. The Gilmer laboratory transgenically expressed the BNYVV P25 protein in Arabidopsis and plants showed more lateral roots than the non-transgenic controls, had higher levels of auxin, and were more responsive to exogenous applications of 2,4-Dichlorophenoxyacetic acid (2,4-D; an auxin analog) [57]. Three genes encoding F-box proteins were upregulated in these transgenic Arabidopsis plants.…”
Section: Hijacking the Host E3 Ub-ligase Using Viral-encoded F Boxmentioning
confidence: 99%